A comparison of different indirect techniques to evaluate volcanic intact rock strength - Del Potro, Rodrigo (2009)
The efficiency of different methods that are used to evaluate volcanic intact rock strength is compared that includes Schmidt hammers, point load tests and uniaxial compression tests. The Schmidt hammer records the rebound height of the mass (R) on a linear scale and gives an indication of the strength of the material being tested. The two types of Schmidt hammers (L- and N-type), with different impact energies are used that shows results as the rebound height RLand RN for the L- and N-type Schmidt hammers, respectively. The other method used is point load test that provides strength measurements of irregular fragments of rocks or of rock cores, with all rock dimensions being greater than 50 mm. The last method is uniaxial compression that shows little scatter and clear logarithmic increase of uniaxial compressive strength with increasing unit weight. The studies showed that Schmidt hammers can give results similar in quality to uniaxial compression tests.